ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine students’ critical thinking skills in mathematics for fifth-grade students at SDN 3 Bojong in the 2025/2026 academic year. The subjects of this study were all 15 students of grade V at SDN 3 Bojong. This research employed a qualitative approach with a descriptive research design.The results of the study indicate that students are categorized into low, medium, and high levels of critical thinking ability. The data collection techniques used in this study were tests and interviews. The data obtained from these techniques were analyzed using the model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing.The findings show that some students were able to answer questions correctly; however, not all students were able to provide clear and systematic explanations or solution steps. In addition, based on the interview results, students still experienced difficulties in communicating their thinking processes fluently and systematically. Therefore, it can be concluded that students’ critical thinking skills in mathematics learning still need to be improved, especially in the aspects of providing reasoning and explaining problem-solving processes.